Floral asymmetry and predation risk modify pollinator behavior, but only predation risk decreases plant fitness - Antiqueira, Pablo Augusto Poleto [UNESP]; Romero, Gustavo Quevedo (Springer Nature, 2016)
Although predators and floral herbivores can potentially decrease plant fitness by changing pollinator behaviors, studies comparing the strength of these factors as well as their additive and interactive effects on pollinator visitation and plant fitness have not been conducted. In this study, we manipulated the floral symmetry and predator presence (artificial crab spiders) on the flowers of the shrub Rubus rosifolius (Rosaceae) in a 2 × 2 factorial randomized block design. We found that asymmetry and predators decreased pollinator visitation (mainly hymenopterans), and overall these factors did not interact (additive effects). The effect of predation risk on pollinator avoidance behavior was 62 % higher than that of floral asymmetry. Furthermore, path analyses revealed that only predation risk cascaded down to plant fitness, and it significantly decreased fruit biomass by 33 % and seed number by 28 %. We also demonstrated that R. rosifolius fitness is indirectly affected by visiting and avoidance behaviors of pollinators. The strong avoidance behavioral response triggered by predation risk may be related to predator pressure upon flowers. Although floral asymmetry caused by herbivory can alter the quality of resources, it should not exert the same evolutionary pressure as that of predator–prey interactions. Our study highlights the importance of considering simultaneous forces, such as predation risk and floral asymmetry, as well as pollinator behavior when evaluating ecological processes involving mutualistic plant-pollinator systems.
Keywords: Flowering plant evolution; Mutualism; Path analysis; Plant reproductive success; Trait-mediated indirect interaction